SPIRITUALITY AND JOB SATISFACTION AMONG THE CONGREGATIO MATER MISERICORDIAE BROTHERS IN INDONESIA PROVINCE: BASIS FOR PSYCHOSPIRITUAL ENHANCEMENT - Perang Blasius (Jurnal Keperawatan Florence Nightingale, 2019)
This research is designed to examine the relationships between spirituality and job satisfaction of the Congregatio Mater Misericordiae (CMM) Brothers in Indonesia Province. In order to determine the profile of spirituality and job satisfaction and their relationship, eighty (80) CMM Brothers was chosen to be respondents. The respondents were living in various convents in Indonesia (Sumatra, Java, Sulawesi, and Kalimantan). The age range of the respondents was 21- 50 and above years old. Assessment of Spirituality and Religious Sentiment (ASPIRES) and Job Satisfaction Survey (JSS) were used as instruments to collect data. The data were analyzed by utilizing descriptive statistics like frequency and percentage distribution, means, standard deviation, Kruskal Wallis Test, and Spearman’s to determine the relationship between the variables. Results revealed that there was no significant relationship between spirituality and job satisfaction. Religiosity and Total Job Satisfaction (r= .151, p= .181), Religious Crisis and Total Job Satisfaction (r= -.173, p .124), Prayer Fulfillment and Total JS with r=.330, p= .003) Universality and Total JS (r .025, p .826), Connectedness and Total JS (r= -.111, p= .327), Spiritual Transcendence and Total JS with r= .109, p = .337. The result of this study will be significant to the CMM Brothers for improving spirituality and job satisfaction.